1965
DOI: 10.1111/j.1528-1157.1965.tb03785.x
|View full text |Cite
|
Sign up to set email alerts
|

The Periodically Recurring Focal Discharge

Abstract: SUMMARY  A rare electrographic pattern of periodically recurring focal discharges, mainly in the parieto‐occipital area, has been described.  The constancy of the rate of discharges under various conditions has been noted. In some patients, the discharge seems to occur at preferential time intervals after the heart beat.  Most of the patients were adults with histories of a seizure disorder, especially with a focal aspect, and also with neurological symptoms, mainly motor deficits, and psychiatric signs, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…The incidence rate of 0.3% of our records with PLEDs was below the reported range of 0.6% to 8.5% of records in older patients. 3,17,19,30 There are no comparable incidence rates for focal periodic discharges of shorter duration than PLEDs in our age group. The incidence of 5% of our neonatal records with focal periodic discharges was more than 16 times the incidence rate of PLEDs in this population.…”
Section: Discussioncontrasting
confidence: 46%
“…The incidence rate of 0.3% of our records with PLEDs was below the reported range of 0.6% to 8.5% of records in older patients. 3,17,19,30 There are no comparable incidence rates for focal periodic discharges of shorter duration than PLEDs in our age group. The incidence of 5% of our neonatal records with focal periodic discharges was more than 16 times the incidence rate of PLEDs in this population.…”
Section: Discussioncontrasting
confidence: 46%
“…From these results, it was concluded that PLEDs carried a different clinical significance for pediatric patients, but this conclusion may have been premature owing to certain limitations of the study. The study sample was small, involving only 7 patients, and the cited adult data were actually derived from mixed-age studies with mean ages in the adult range but with inclusion of children as young as 3 years of age (Chatrian et al, 1964;Hughes and Schlagenhauff, 1965;Schwartz et al, 1973). We examined this early pediatric study against a better defined adult population and our larger series of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic lateralized epileptiform discharges (PLEDs), a term coined by Chatrian et al (1964), are an electroencephalographic (EEG) phenomenon consisting of unilateral or focal spikes or sharp wave complexes occurring in a pseudoperiodic fashion, usually at a rate of 1-2 s. The most common etiology of PLEDs is an acute or subacute hemispheric or focal cerebral lesion, but PLEDs also occur in patients with a chronic static cerebral lesion or chronic epilepsy (Chatrian et al, 1964;Hughes and Schlagenhauff, 1965;Markand and Daly, 1971;Schwartz et al, 1973;Dauben and Adams, 1977;Erkulvrawatr, 1977;Porecha and Reilly, 1977;PeBenito and Cracco, 1979;Schraeder and Singh, 1980;de la Paz and Brenner, 1981;Westmoreland et al, 1986). Investigation of regional cerebral blood flow (rCBF) and local cerebral metabolic ratio (LCMR) by using positron emission computed tomography (PET) or single-photon-emission computed tomography (SPECT) provides valuable information about the pathophysiology of epilepsy, which is complementary to the findings of electrophysiologic studies (Kuhl et al, 1980;Engel et al, 1982;Mazziottaand Engel, 1984).…”
Section: Discussionmentioning
confidence: 99%